2021
DOI: 10.3390/molecules26092616
|View full text |Cite
|
Sign up to set email alerts
|

Bee Bread Can Alleviate Lipid Abnormalities and Impaired Bone Morphology in Obese Zucker Diabetic Rats

Abstract: This study examined for the first time whether bee bread (BB, consisting of monofloral rape bee pollen) could alleviate lipid derangements and reduced bone quality in Zucker diabetic fatty (ZDF) rats, which are considered an appropriate animal model for type 2 diabetes mellitus (T2DM) investigation. Adult ZDF rats were segregated into four groups: lean non-diabetic rats (L group), obese diabetic rats untreated (C group), and those treated with the BB at two doses (500 and 700 mg/kg body weight, respectively, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…It is therefore surprising that bee products have the ability to alleviate diabetic complications, including the improvement of damaged bone structure. Martiniakova et al [ 108 ] reported a protective effect of bee bread against hyperglycemia and diabetic bone disease in Zucker diabetic fatty rats. In addition, honey can also improve glycemic control and reduce diabetic complications [ 109 ] due to a wide range of proteins, bioactive peptides, fatty acids, organic acids, phenolic acids, prebiotics, probiotics, fiber, minerals, vitamins, flavonoids and carotenoids.…”
Section: Macronutrients and Osteoporosismentioning
confidence: 99%
“…It is therefore surprising that bee products have the ability to alleviate diabetic complications, including the improvement of damaged bone structure. Martiniakova et al [ 108 ] reported a protective effect of bee bread against hyperglycemia and diabetic bone disease in Zucker diabetic fatty rats. In addition, honey can also improve glycemic control and reduce diabetic complications [ 109 ] due to a wide range of proteins, bioactive peptides, fatty acids, organic acids, phenolic acids, prebiotics, probiotics, fiber, minerals, vitamins, flavonoids and carotenoids.…”
Section: Macronutrients and Osteoporosismentioning
confidence: 99%
“…In the same context, Martiniakova et al [ 109 ] reported that the oral administration of monofloral bee bread extract ( Brassica napus L.) significantly lowered blood glucose levels, prevented lipid abnormalities, and impaired the bone morphology of Zucker diabetic fatty rats. In addition, Haščík et al [ 110 ] showed the effect of dietary bee bread powder on the chemical composition of Japanese quails meat.…”
Section: The Pharmacological Effect Of Bee Bread: In Vivo Investigationsmentioning
confidence: 99%
“…In addition, vitamins (e.g., B and E) and minerals (e.g., Mg, zinc (Zn), and selenium (Se)) found in whole grains can reduce oxidative stress and inflammation [ 36 ]. Capcarova et al [ 37 ] and Martiniakova et al [ 38 ] state the protective impact of bee bread against hyperglycaemia, hyperlipidaemia, and diabetic bone disease in the appropriate T2DM animal model. Moreover, the most famous bee product, honey, can also improve glycaemic control and reduce secondary diabetic complications [ 39 ].…”
Section: Treatment Of Type 2 Diabetes Mellitusmentioning
confidence: 99%